Magnetic properties of DCNQI salts studied using mu SR - Pratt, F; Pattenden, P; Blundell, S; Chow, K; Jestadt, T; Hayes, W; Kato, R; Tamura, M; Sawa, H; Kashimura, Y (1997)
Examples from the (R-1,R-2-DCNQI)(2)X family of molecular conductors have been studied using mu SR in order to provide information about the microscopic magnetic properties of the various phases. For the fully deuterated dimethyl Cu salt (d(8)-DMe-Cu) there is a metal-insulator (MI) transition around 80 K and a magnetic transition around 7 K. The muon spin relaxation rate becomes enhanced in the region of the MI transition and below, reflecting the quenching of valence fluctuations and the appearance of localised spins on the Cu sites. A zero field precession signal develops below 7 K as a result of the 3D magnetic ordering of the Cu spins; the field distribution derived from the precession frequency is consistent with the proposed magnetic structure. In addition to the zero field studies, nuclear quadrupolar level crossing resonance between the muon and the imine nitrogen of the DCNQI has been used to study the temperature dependence of the electronic stale of the molecular conductor.